Human regulatory T cells locally differentiate and are functionally heterogeneous within the inflamed arthritic joint. Issue 10 (30th September 2022) - Lutter, Lisanne; van der Wal, M Marlot; Brand, Eelco C; Maschmeyer, Patrick; Vastert, Sebastiaan; Mashreghi, Mir‐Farzin; van Loosdregt, Jorg; van Wijk, Femke
Abstract: Objective: Tregs are crucial for immune regulation, and environment‐driven adaptation of effector (e)Tregs is essential for local functioning. However, the extent of human Treg heterogeneity in inflammatory settings is unclear. Methods: We combined single‐cell RNA‐ and TCR‐sequencing on Tregs derived from three to six patients with juvenile idiopathic arthritis (JIA) to investigate the functional heterogeneity of human synovial fluid (SF)‐derived Tregs from inflamed joints. Confirmation and suppressive function of the identified Treg clusters was assessed by flow cytometry. Results: Four Treg clusters were identified; incoming, activated eTregs with either a dominant suppressive or cytotoxic profile, and GPR56 + CD161 + CXCL13 + Tregs. Pseudotime analysis showed differentiation towards either classical eTreg profiles or GPR56 + CD161 + CXCL13 + Tregs supported by TCR data. Despite its most differentiated phenotype, GPR56 + CD161 + CXCL13 + Tregs were shown to be suppressive. Furthermore, BATF was identified as an overarching eTreg regulator, with the novel Treg‐associated regulon BHLHE40 driving differentiation towards GPR56 + CD161 + CXCL13 + Tregs, and JAZF1 towards classical eTregs. Conclusion: Our study reveals a heterogeneous population of Tregs at the site of inflammation in JIA. SF Treg differentiate to a classical eTreg profile with a more dominant suppressive or cytotoxic profile that share a similar TCR repertoire, or towards GPR56 + CD161 + CXCL13 + Tregs with a more distinct TCR repertoire. Genes characterising GPR56 + CD161 + CXCL13 + Tregs were also mirrored in other T‐cell subsets in both the tumor and the autoimmune setting. Finally, the identified key regulators driving SF Treg adaptation may be interesting targets for autoimmunity or tumor interventions. Abstract : We show that human regulatory T cells (Tregs) within the inflamed arthritic joint differentiate locally and are functionally heterogeneous. Tregs differentiate towards either classical effector Tregs or towards GRP56 + CD161 + CXCL13 + Tregs, supported by TCR data. Novel predicted drivers of local Treg differentiation include JAZF1 for classical effector Tregs and BHLHE40 for GRP56 + CD161 + CXCL13 + Tregs.